Physical and technical-tactical performance in judo athletes with visual impairments: analysis from official competitions and validity of a specific protocol - Kons, Rafael Lima (2021)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2021.